PERAN POLITIK KIAI DALAM PROSES POLITIK DI PARTAI POLITIK (Studi Kasus Peran KH. A. Haris Shodaqoh di Partai Persatuan Pembangunan) - ULIN NUHA, ULIN NUHA (Program Magister Ilmu Politik, Universitas Diponegoro, 2012)
Abstract Since the passing of the reform party brings a lot of the principles of Islam as an ideological platform and the foundation of the party. This seems in line with the kiai activities to disseminate the teachings of Islam. Of course the inevitable happened